New record of a rarely collected caridean shrimp Bathypalaemonella pandaloides (Rathbun, 1906) (Decapoda: Bathypalaemonellidae) from the West Mariana Ridge, northwestern Pacific - Komai, Tomoyuki; Tsuchida, Shinji; Fujiwara, Yoshihiro (Zootaxa, 2022)
The deep-sea caridean shrimp Bathypalaemonella pandaloides (Rathbun, 1906) (Bathypalaemonellidae) was heretofore known only from Hawaii (type locality) and French Polynesia. In this article, we report this rarely collected species on the basis of a single male specimen from the Ritto Seamount on the West Mariana Ridge, northwestern Pacific, at a depth of 657 m, collected by means of a remotely operated vehicle (ROV). The specimen is intact, enabling us to describe the characteristic major pereopod 2 of the species for the first time. The closest relative is B. zimmeri Balss, 1914, known only from the western Indian Ocean; fewer accessory spiniform setae on the pereopods 3–5 dactyli and the less produced distal lamella of the antennal scaphocerite distinguish B. pandaloides from B. zimmeri. K2P divergences of the mitochondrial COI and 16S rRNA genes in taxa attributed to Bathypalaemonella Balss, 1914 are presented. The present specimen was collected from an anthipatharian octocoral colony, Leiopathes sp. (Cnidaria), suggesting a commensal relationship.